The effect of the online flipped classroom on self-directed learning readiness and metacognitive awareness in nursing students during the COVID-19 pandemic - Safoura Khodaei; Shirin Hasanvand; Mohammad Gholami; Yaser Mokhayeri; Mitra Amini (BMC, 2022)
Abstract Background The COVID-19 pandemic has initiated digital developments in higher education while closing in-person university classes. As this crisis continues, the need to revive virtual learning opportunities was seriously felt. The present study was conducted to determine the online flipped classroom's effect on nursing students' self-directed learning readiness and metacognitive awareness. Methods This quasi-experimental single-group study with pretest-posttest design recruited 34 sophomore students of a nursing school in Lorestan province, Western Iran selected by census according to the inclusion criteria. Online asynchronous learning and online flipped classrooms were used during the semester's first and second eight weeks, respectively. Students filled out self-directed learning readiness scale and metacognitive awareness inventory online before, in the middle of, and at the end of the semester. Data were analyzed using paired t-test in Stata-14 software. Results There was no significant difference between the mean score of metacognitive awareness before and after Online asynchronous learning (P=0.15), but the mean score of self-directed learning readiness increased significantly after OA (P=0.0004). After applying online flipped classrooms, students' mean (SD) scores of metacognitive awareness and self-directed learning readiness were 272.03 (53.03) and 162.03 (21.77), respectively, which confirmed their significant improvement compared to before the intervention. A comparison of the mean score changes of both methods indicated that their implementation did not lead to significant differences between the mean total score of metacognitive awareness (P=0.15) and the mean total score of self-directed learning readiness (P=0.07). Discussion Online flipped classroom approach can be used as an effective method in nursing education by improving self-directed learning and metacognitive awareness, which are essential in online education for nursing students.